The dynamics of energy communities and innovative cooperatives: Mapping current knowledge and future trends - Hua Depeng; Fracisco Javier S. Lacarcel; Virginia Simón-Moya (Journal of Innovation & Knowledge)
Cooperative forms of organization have led to major advances in energy use in the last decade. A common cooperative form in the energy sector is that of energy communities. These energy communities produce, distribute, and consume their own sustainable energy. To explore this cooperative structure and create knowledge on the topic, this study presents a comprehensive bibliometric analysis of the scientific literature on energy communities and cooperatives. Using bibliographic coupling, co-citation analysis, and keyword co-occurrence, the analysis identifies key themes and interconnections in this research field. The findings reveal major focus areas and key characteristics, including renewable energy, community energy, energy transition, policy, participation, governance, and innovation. The study highlights the importance of integrating technological innovation, community involvement, and cooperative models to advance sustainable energy systems in energy communities. Finally, this study makes a unique contribution through its holistic mapping of the research landscape. It thus provides an original synthesis of key themes and gaps in the literature. The proposal of seven future research directions, 14 research objectives, and 21 research questions creates a comprehensive framework designed to guide future academic inquiry and inform policy and practice in the evolving field of energy communities and cooperatives.